Sedimentasi Identitas Keislaman: Potret Living Qur’an Masyarakat Petani di Madura - Alfan Shidqon; Ramadhan, Riqqi (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2023)
This study investigates the presence of the Qur'an within the agricultural community of Madura. The study of the living Quran encompasses the reception of the Qur'an in the practical context of farming in Madura. This research examines the way in which the Qur'an is experienced and practiced within a specific community, focusing on its performative nature and positioning it under the frame of discursive tradition. The research aims to address two main questions: firstly, what are the many modes of Qur'an performance among the agricultural community in Madura; and secondly, how does the discursive tradition around these performances manifest itself. This study is grounded in a field investigation that gathers data through interviews, observations, and supplementary literature reviews. This article contends that the Qur'an serves as both a prayer and an integral part of the daily life of the farming community in Madura, from the pre-farming stage to harvesting. Additionally, it highlights the pivotal role of the kiai in transmitting Islamic teachings, resulting in the development of traditions that are prevalent among the Madurese community.